Antiproliferative Effect of Grammatophyllum speciosum Ethanolic Extract and Its Bioactive Compound on Human Breast Cancer Cells - Verisa Chowjarean; Kamala Sadabpod (The Scientific World Journal)
Background/Aim. Grammatophyllum speciosum Blume exhibits various promising pharmacological activities. However, its effect on breast cancer has not been determined. Materials and Methods. The antiproliferation effects of the G. speciosum pseudobulb ethanolic extract (GSE) and isovitexin (bioactive constituent) were investigated on the MCF-7 human breast cancer cell line using MTT and colony formation assay. The expression levels of proliferation-regulatory proteins were determined by western blotting. Results. Noncytotoxic concentrations of GSE significantly suppressed the proliferation of MCF-7 cells. Tumor colony formation decreased in both number and size. The level of phosphorylated AKT and β-catenin was suppressed by GSE treatment. Antiproliferation was observed in isovitexin-treated MCF-7 cells in the form of inhibited colony formation and reduced expression of phosphorylated AKT and β-catenin protein. Conclusions. This study demonstrates the novel effect of G. speciosum as an antiproliferative via suppression of the AKT/β-catenin-dependent pathway. This may prompt further investigation of this plant in breast cancer therapy.